Factor analysis of the relationship of curiosity and device addiction through motivation to digital literacy in the context of smart learning - Yeka Hendriyani; Muhammad Anwar; Hendra Hidayat; Elsa Sabrina; Pardjono Pardjono; Erni Marlina Saari (Jurnal Pendidikan Vokasi, 2023)
This study aims to investigate the relationship between curiosity and device addiction factors and motivation towards digital literacy in the context of smart learning. This study used a qualitative approach involving 228 students majoring in Electronics Engineering Education at Universitas Negeri Padang. Data were collected through a Likert-scale questionnaire with a saturated sampling method, ensuring all relevant respondents were involved. To evaluate the measurement model of the research questions, Structural Equation Modeling (SEM) analysis was used. The results revealed that digital literacy is significantly influenced by three main factors: curiosity, gadget addiction and app addiction. Furthermore, the study found that curiosity-driven motivation tends to improve digital literacy, while gadget and app addiction have a negative impact. These findings provide valuable insights for curriculum development, especially in improving digital literacy among electrical engineering education students. In addition, this study highlights the importance of educational interventions that can manage the wise use of technology and promote constructive curiosity. This research contributes to the understanding of how curiosity and excessive use of technology can affect digital literacy skills, which are crucial to face the challenges of the Industrial Revolution 4.0 era. Thus, the results of this study can serve as a basis for more effective educational strategies in preparing students for future digital challenges.